Expression and significance of p120ctn isoforms in lung squamous cell carcinomas - Enhua WANG; Yan WANG; Yang LIU; Yuan MIAO (Chinese Journal of Lung Cancer, 2008)
Background and Objective It has been proven that p120ctn plaied an important role in cell adhesion and correlates with tumorigenesis significantly, the aim of this work is to investigate the expression of p120ctn(p120 catenin) isoform proteins in lung squamous cell carcinomas and adenocarcinomas, and analyze the correlations between p120ctn and clinicopathological parameters. Methods Immunofluorescence and Westren Blot were used to detect the expression of p120ctn isoforms in lung cancer tissues and the corresponding normal lung tissues. ResultsCompared to normal epithelium of lung, lung cancer tissues show reduction or absence of membrane expression or cytoplasmic accumulation of p120ctn. In normal lung tissues, the total levels of p120ctn proteins were significantly higher than that in lung cancer tissues (P <0.001). The isoform 1 (120KD) and isoform 3 (100KD) proteins were the major isoforms of p120ctn expressed in normal lung tissues, which were significantly reduced in lung cancer samples (P =0.001 andP <0.001, respectively). Furthermore, the changes in isoform 3 protein levels was negatively associated with lymph node metastasis (P =0.005). Conclusion Reductions of p120ctn isoform 1 and 3 is a common phenomenon in lung cancer tissues and may play a role in metastasis progression in human lung cancer.